Consumers' reaction to product variety: Does culture matter? - Ahmed, Sayed; Uddin, Md Mohan; Ahshanullah, Mohammad (2008)
Substantial cultural variations should be considered in establishing marketing strategies around the world.This paper stresses several aspects.Initially, consumers’ perceptions of variety differ from the actual variety provided by a manufacturer or retailer.Literature indicates that consumers’ benefits and costs of perceived variety differ systematically across cultures.Current cultural theory suggests that they also encounter greater cognitive and emotional costs than individuals in collectivistic cultures when ultimately choosing.The objective of this paper is to point out specific implications.First, theories on variety perception have been discussed in order to highlight consumers’ benefits and costs of variety.Second, an attempt is made to find out whether culture-oriented market has facilitated the successful acceptance of product by the consumers around the world or not.